2016
DOI: 10.1007/s12325-016-0352-3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intravoxel Incoherent Motion MRI in Predicting Early Treatment Response to Chemoradiation for Metastatic Lymph Nodes in Nasopharyngeal Carcinoma

Abstract: The present study indicated that the initial f value may be more accurate than the initial D*, D, and ADC in the early prediction of treatment response to chemoradiotherapy for metastatic lymph nodes in patients with NPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 27 publications
5
13
0
Order By: Relevance
“…Common MRI ways of assessing the response to therapy are DCE-MRI and DWI. Recently, many studies focused on the use of the IVIM bi-exponential model for the same purpose and labeled the non-invasive method to be more accurate than DWI by giving separate diffusion- and perfusion-related parameters (Granata et al, 2015; Lu et al, 2016; Shirota et al, 2016; Lee et al, 2017; Yang et al, 2017). The areas of necrosis might increase in the diffusion-weighted coefficient and perhaps mislead the assessment of the response of a tumor to therapy (Bains et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Common MRI ways of assessing the response to therapy are DCE-MRI and DWI. Recently, many studies focused on the use of the IVIM bi-exponential model for the same purpose and labeled the non-invasive method to be more accurate than DWI by giving separate diffusion- and perfusion-related parameters (Granata et al, 2015; Lu et al, 2016; Shirota et al, 2016; Lee et al, 2017; Yang et al, 2017). The areas of necrosis might increase in the diffusion-weighted coefficient and perhaps mislead the assessment of the response of a tumor to therapy (Bains et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…After screening the titles and abstracts, 22 articles were considered potentially eligible after excluding 108 articles for the following reasons: non-English articles (n = 22), case reports (n = 9), not in the field of interest (n = 56), non-original articles (i.e., reviews, letters, editorials, conference abstracts) (n = 18), and non-human studies (n = 3). After full-text review, nine articles were further excluded because they were not in the field of interest (n = 1) 28 , had overlapping study populations (n = 2) 10 , 29 , had insufficient information for the reconstruction of 2 × 2 tables (n = 1) 30 , insufficient detail of pretreatment ADC (n = 3) 31 33 , or region of interest was on lymph nodes only (n = 2) 34 , 35 . Thirteen original studies were included for qualitative synthesis 5 , 6 , 8 , 9 , 11 19 .…”
Section: Resultsmentioning
confidence: 99%
“…These discoveries corroborated with the ideas of Yu, who suggested that non-residual group also had lower ADC-pre than the residual group [ 20 ]. The role of ADC values in predicting treatment response to chemoradiotherapy was also proven in metastatic lymph nodes in patients with NPC [ 8 ]. King et al found that the primary tumor showed significantly lower increase in percentage change of mean ADC for local failure than for local control [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The advances in imaging modalities have led to improving the ability of diagnosing NPC [ 7 ], predicting and assessing tumor responding to treatment [ 8 12 ]. The apparent diffusion coefficient (ADC) which represents cellularity and interstitial water mobility is calculated by diffusion weighted imaging (DWI) using mono-exponential model reflecting Gaussian diffusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation